The contribution of An Interactive Multimedia in Teaching Simple Present Tense for Junior High Student - Djoko Sri Bimo (Linguists : Journal Of Linguistics and Language Teaching, 2020)
Learning English in Junior High School emphasizes on four language skills, they are speaking,writing, reading,and listening. However, it sometimes collides with the complexity of grammar, one of which is learning the present simple present tense in which for some people is acomplicated matter and makes it difficult for them in understanding English. Departing from this problem, a new breakthrough is needed, so that students are interested in learning English. Today’s education emphasizes on how to learn by utilizing technological sophistication, then Multimedia is one of the technologies that can be used to stimulate thoughts, feelings, concerns, and  abilities or skills of  learners. This technology has a very positive impact on students since it can provide solutions and ease in carrying out the learning process. The purpose of the study was to describe the implementation of interactive multimedia and to describe the level of defiance  of the eighth grade students of SMP Muhammadiyah I Surakarta in learning of Simple Present Tense.  The study employed a quantitative research approach, and the type used was an experiment. The experimental design in this study was randomized pre-test post-test design. The sample in this study was class VIII A, assigned as the Experiment Group 1 (EG1) who was taught by using interactive multimedia, while class VIII B, assigned as the Experimental Group 2 (EG2) who was taught by  using the lecturing method and supported by using a handout. After learning was complete, both groups were given the same post-test. The result found that the EG1 who given treatment by using interactive multimedia got higher results than the EG2 who treated by Handout, where the mean score of the EG1 was 83.04, while the mean score of the EG2 was 72.96. Based on the result above, it was indicated that the students of SMP Muhammadiyah I Surakarta was more comprehend in learning The Simple Present Tense by using interactive multimedia better than conventionally, since interactive multimeda can build their creativity power and increase their understanding in English.